Toward a land zoning negotiation support platform: “Tips and tricks” for participatory land use planning in Laos - Bourgoin, Jeremy; Castella, J.C.; Pullar, D.; Lestrelin, Guillaume; Bouahom, B. (Elsevier, 2012)
Managing complex landscape mosaics in areas dominated by poverty often requires addressing conflicting objectives and managing trade-offs, such as that between maintaining/enhancing ecological functions and improving livelihoods. Laos, like many other developing countries dependent on agriculture and natural resources for the subsistence of a mostly rural population, has used land use planning (LUP) as a core policy instrument to achieve sustainable development. However, previous reviews of LUP implementation showed large discrepancies between policies and practices and between the intended goals and actual outcomes. There is a need for increased participation, improved integration of scales, harmonization of superimposed plans, and enhanced coordination between implementing agencies and other stakeholders. Consequently, former normative approaches to LUP have been gradually replaced (at least on paper) by a new paradigm. Participatory land use planning (PLUP) has recently become a central element of donor-supported programs in developing countries. However, despite the good intentions of PLUP principles, implementation remains entangled with confused practical issues that compromise effective participation. As an alternative to complex, technologically sophisticated LUP models that local stakeholders cannot use or replicate, a communication platform supporting negotiations among multiple stakeholder groups was tested in a village cluster in Luang Prabang Province in northern Laos. This innovative approach, based on a combination of role-playing games, participatory 3D modeling, GIS, and socioeconomic and environmental impact assessment, allows stakeholders to collectively explore the consequences of land use decisions and choose between alternative future landscapes.